2020
DOI: 10.17645/pag.v8i3.2995
|View full text |Cite
|
Sign up to set email alerts
|

Can EU Civil Society Elites Burst the Brussels Bubble? Civil Society Leaders’ Career Trajectories

Abstract: The Brussels-based civil society organizations (CSOs) have been conceived by the EU to act as a bridge between the bureaucratic elites and the citizens of Europe. The institutionalized presence of the major EU-based CSOs has, however, called their legitimacy into question, as exemplified by notions such as ‘revolving doors’ implying homogeneous social, educational, and professional backgrounds shared by both EU officials and CSO leaders. This article therefore asks the following questions: To what extent do th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…We have selected the EU as a supra-national context for civil society mobilisation and organising (Johansson and Kalm, 2015;Meeuwisse and Scaramuzzino, 2018), since studies have shown that EU-level population groups are comparable to national level-population groups, due to sufficient similarity in terms of organisational types and representational capacity (see Berkhout et al, 2017;Heylen et al, 2020;Meeuwisse and Scaramuzzino 2017). Also, similar to national civil societies, processes of resource stratification and centralisation have been detected at the EU level (Lindellee and Scaramuzzino, 2020).…”
Section: Selection Of Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…We have selected the EU as a supra-national context for civil society mobilisation and organising (Johansson and Kalm, 2015;Meeuwisse and Scaramuzzino, 2018), since studies have shown that EU-level population groups are comparable to national level-population groups, due to sufficient similarity in terms of organisational types and representational capacity (see Berkhout et al, 2017;Heylen et al, 2020;Meeuwisse and Scaramuzzino 2017). Also, similar to national civil societies, processes of resource stratification and centralisation have been detected at the EU level (Lindellee and Scaramuzzino, 2020).…”
Section: Selection Of Countriesmentioning
confidence: 99%
“…Top civil society leaders are today prominent actors as they are formally and personally charged with the key tasks of maintaining and representing powerful organisations. Over the last several decades, increased resource stratification in European civil societies has led to the disproportionate concentration of political and economic resources in the hands of a small group of large civil society organisations (hereafter CSOs) (Johansson and Uhlin, 2020; Lindellee and Scaramuzzino, 2020). Organisations like Amnesty International, Greenpeace, Oxfam, Friends of the Earth, the World Wildlife Fund, and Caritas are examples of major players in their respective contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of civil society leaders’ career trajectories are few. While some studies from the US have focused on the career trajectories of executive leaders in the non-profit sector (Norris-Tirrell et al, 2018; Suarez, 2010), studies of presidents’ or chairpersons’ career trajectories are very few (see Lindellee & Scaramuzzino, 2020 for an example). This might be a consequence of the fact that the presidents are often understood as voluntary or unpaid leaders compared to the employed, paid executive leaders (cf.…”
Section: Introductionmentioning
confidence: 99%
“…In their combined effort, the contributors show that civil society elites can be found across the world. The different contributions also apply various methods to study civil society elites, ranging from statistical analysis of survey data (Gulbrandsen, 2020) via qualitative analysis of biographical data on individual civil society leaders (Lindellee & Scaramuzzino, 2020) to qualitative interviews (the other contributions).…”
mentioning
confidence: 99%
“…Four of the contributions (Haryanto, 2020;Lay & Eng, 2020;Lindellee & Scaramuzzino, 2020;Norén-Nilsson & Eng, 2020) draw explicitly on Bourdieu's field theory and the related concept of capital. This approach is useful because it sheds light on relations of conflict and cooperation within civil society and how different power resources are valued, gained and used by civil society actors, thus indicating how and why certain actors emerge as elites.…”
mentioning
confidence: 99%